Surgical treatment of aspergillus fumigatus spondylitis in a cirrhotic patient: a rare case report - Yunlong Zhou; Zhiqiang Liu; Hui Yu; Guiying Guo; Xing Yang; Junyu Zhang (BMC Infectious Diseases)
Abstract Background Fungal spondylitis often occurs in patients with immune dysfunction, and its diagnosis and treatment pose certain challenges. However, even in immunocompromised patients, Aspergillus spondylitis remains rare. This case reports the diagnostic and therapeutic experience of fungal spondylitis in a patient with consolidated cirrhosis and no significant immune impairment. Case presentation A 45-year-old agricultural worker had chest and back pain for 6 months. The patient’s pain was a persistent dull ache that worsened with chronic coughing and postural changes and decreased when he was laying down. Based on the patient’s clinical presentation, biochemical tests and imaging, considered possible spinal tuberculosis. Empirical anti-tuberculosis treatment was not successful. Due to the failure of medication and the formation of an epidural abscess, the decision was made to proceed with surgical treatment. Intraoperative tissue specimens were subjected to high throughput testing for culture, tuberculosis gene X-pert and high-throughput detection of macro-gene infectious agents. It was confirmed that the spinal infection was caused by Aspergillus fumigatus. Tuberculosis medication was ceased and antifungal therapy with voriconazole was started. Three months after surgery, the patient recovered well with no fever or pain. Discussion and conclusion In summary, in addition to patients with low immune function who should be evaluated for fungal spondylitis, patients with infectious diseases of the spine who are immunocompetent but have comorbid cirrhosis should be evaluated when treatment fails. If the diagnosis cannot be made by conventional or unconventional methods, surgical methods should be used in a timely manner for diagnosis and treatment.